(untitled) (Third Sector Social Economic Review, 2019)
The purpose of this study is to examine the mediator role of organizational commitment in the relationship between ethical leadership and counterproductive work behaviour. The datas of this study were obtained with survey method from 253 employees working in different departments in a firm that shows activity in the construction sector in Turkey. Correlation and regression analysis were applied by SPSS 23 programme. The results reveal that ethical leadership has a positive relationship with organitaional commitment; and negatif relationship with counterproductive work behaviour. Also, there is a negatif relationship between organizational commitment and counter-prductive work behaviour. Another result of the study is organitaional commitment has a mediating effect on the relationhip between ethical leadership and counterproductive work behaviors.